The Later Career of George Wither. - Hensley, Charles Stanley (Berlin/Boston : De Gruyter, Inc., 1969)
No detailed description available for "The later career of George Wither".
Intro -- Introduction -- I. The Sharp-Eyed Satirist -- II. Britain's Remembrancer -- III. The Belated Humanist -- IV. The Tireless Pamphleteer -- Bibliography.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Poets, English--Early modern, 1500-1700--Biography.; Electronic books